2022
DOI: 10.1101/2022.11.08.515698
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The locus coeruleus broadcasts prediction errors across the cortex to promote sensorimotor plasticity

Abstract: Prediction errors are differences between expected and actual sensory input and are thought to be key computational signals that drive learning related plasticity. One way that prediction errors could drive learning is by activating neuromodulatory systems to gate plasticity. The catecholaminergic locus coeruleus (LC) is a major neuromodulatory system involved in neuronal plasticity in the cortex. Using two-photon calcium imaging in mice exploring a virtual environment, we found that the activity of LC axons i… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 71 publications
0
5
0
Order By: Relevance
“…In addition, NE may exert its effects on both neuronal and non-neuronal cells (Paukert et al, 2014; Mu et al, 2019), providing a rich substrate for broadcasting an ascending learning signal across large volumes of cortex. This learning signal may generalize beyond reinforcement learning; artificial excitation of LC changes sensory-driven learning as well (Glennon et al, 2019; Jordan and Keller, 2022; McBurney-Lin et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, NE may exert its effects on both neuronal and non-neuronal cells (Paukert et al, 2014; Mu et al, 2019), providing a rich substrate for broadcasting an ascending learning signal across large volumes of cortex. This learning signal may generalize beyond reinforcement learning; artificial excitation of LC changes sensory-driven learning as well (Glennon et al, 2019; Jordan and Keller, 2022; McBurney-Lin et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Prior work has demonstrated that LC neurons and axons fire synchronously to aversive events and prediction errors ( Uematsu et al, 2017 ; Breton-Provencher et al, 2022 ; Jordan and Keller, 2022 ) but that axons can be asynchronous for appetitive events ( Breton-Provencher et al, 2022 ). We hypothesized that these distinct patterns of LC NE neuronal activity (local asynchronous and global synchronous) might be reflected at cellular scale within the mPFC in the temporal correlations of local and global NE fields.…”
Section: Resultsmentioning
confidence: 99%
“…The spatial autocorrelation was approximated well by a double exponential model, indicating that local NE correlations fall off with spatial distance (Fig.2C). These dynamics thus appeared compatible with a model in which diffusive spread of NE from release sites contributes to variation in local NE dynamics.Prior work has demonstrated that LC neurons and axons fire synchronously to aversive events and prediction errors(Breton-Provencher et al, 2022;Jordan & Keller, 2022;Uematsu et al, 2017), but that axons can be asynchronous for appetitive events(Breton-Provencher et al, 2022). We hypothesized that these distinct patterns of LCNE neuronal activity (local asynchronous and global synchronous) might be reflected at cellular scale within mPFC in the temporal correlations of local and global NE fields.…”
mentioning
confidence: 89%
“…Alternatively, errors could be computed in the pulvinar or in V1 from the comparison of visual input with predictions conveyed by top-down input from higher-order cortical areas [5][6][7][8][9][10]14 , and amplified through pulvinar-V1 recurrent connections. Either way, signals in V1 may be further enhanced by neuromodulators such as acetylcholine or noradrenaline 28,46 that may signal stimulus saliency and novelty, or surprise more generally 51,52 .…”
Section: Discussionmentioning
confidence: 99%